Fortification of Mangrove Crab Shell Flour (Scylla serrata) as a Mineral Source in Functional Cookie Formulation - Widnyani, Ida Ayu Putu Ary; Putra, Anak Agung Ngurah Dwi Ariesta Wijaya (Jurnal Pijar Mipa, 2024)
The importance of calcium and magnesium intake for health, especially bones, teeth, and the nervous system, encourages the development of functional food products rich in minerals. Mangrove crab shell (Scylla serrata) is a waste with calcium-magnesium content that is beneficial for health. This study aims to determine the potential calcium and magnesium content in cookies fortified with mud crab shell flour. The research design used a complete randomised design (CRD). Crab shell flour fortification concentration was 0%, 3%, 6%, 9%, 12%, 15%. Repetition was done 4 times. Data were analysed using the variance analysis (ANOVA) method. The results significantly affected increased calcium and magnesium levels of cookies fortified with mud crab shell flour. The calcium content of cookies ranged from 65.325 – 1,802.773 mg/kg, and magnesium in cookies ranged from 82.719 – 188.553 mg/kg, so cookies with the fortification of mangrove crab shell flour can be used as an alternative functional food product for calcium and magnesium mineral sources.